Stabilization of linear systems with direct feedthrough term in the presence of output saturation. (March 2017) - Zuo, Zhiqiang; Luo, Qiaoyu; Wang, Yijing
Abstract: This paper investigates the stabilization problem for controllable and observable linear systems with saturated outputs, in which direct feedthrough term is involved. The necessity of considering the direct feedthrough term is clarified. We present a constructive design strategy to achieve globally asymptotic stability of the systems by output feedback. The controller is continuous during the interval we drive a specific output component out of saturation in order to handle the direct feedthrough term. Moreover, the parameters to be designed for the controller have close relationship with the transfer function and direct feedthrough matrix. Numerical simulations are included to illustrate the effectiveness of theoretical results.